Perbaikan Produksi, Promosi dan Pemasaran Pada UKM Pengrajin Kue di Kotamobagu Sulawesi Utara dalam Menghadapi Masa Pandemi Covid-19 - Fatimah, Feti; Pomalingo, Moh. Fikri; Tambas, Jane Sulinda; Gugule, Sanusi; Tallei, Trina E. (Solidaritas: Jurnal Pengabdian, 2021)
The COVID-19 pandemic has hit almost all countries and has an impact on various sectors, one of which is the economy and business. The impact of Covid 19 in the economic and business sectors is felt by Small and Medium Enterprises (SMEs). Cake craftsmen in Kotamobagu, North Sulawesi, are one of the SMEs that have been badly affected by the Covid-19 pandemic. Based on the situation analysis, it is known that there are several things that affect the situation, namely: 1. Consumers' fear of unhygienic food products, 2. The closing of shops which are usually used as places to store their merchandise, and 3. Not familiar with online promotion and marketing. Based on this, the objectives of the PKM activity are: to provide assistance to cake-making SMEs in Kotamobagu in order to minimize the impact of the pandemic through improved production, promotion and online marketing. This PKM activity was carried out by involving 10 SMEs in Kotamobagu. The implementation of the activity consists of several stages, namely the preparation stage including the formation of SME groups, the socialization stage includes learning about how to produce cakes using health protocols, and the implementation stage, namely cake production using the Health protocol, making promotional documents and online marketing (making videos and product photos), as well as creating Facebook, Instagram and Youtube accounts. Based on the activities that have been carried out, it is known that this activity is very useful because it is able to produce production improvements, promotions and marketing for SMEs cake craftsmen in Kotamobagu. The output of this activity is the existence of promotional documents and online marketing, through FB, Instagram and Youtube media. The next activity is recommended to conduct training activities with the aim of accelerating the production process, improving product packaging and enriching the variety of superior products to be marketed with a wider target consumer.